História do Ensino Secundário no Ceará: Entre Documentos, Revistas, Jornais e Memórias do Colégio Militar de Fortaleza (1962-1968) - Mesquita, Simone Vieira de (2011)
This dissertation presents the History of Ceará‘s Military Teaching, with emphasis to the Middle Military Teaching, ever since Fortaleza‘s Military School is founded in 1962, an institution that offered us primary-researching source and that made possible a study of its past by allowing attending to its current-regular curricular activities. It shows that the School got consolidated as it follows its predecessor-institutions‘ steps: Ceará‘s Military School (1889), Ceará‘s Military School (1919), Preparatory School of Fortaleza (1942). In order to accomplish this dissertation, we used as historiographical references authors like Adriana Lopez, Carlos Guilherme Mota, Boris Fausto, Nelson Werneck Sodré, João Batista Magalhães e Plácido Aderaldo Castelo. P. A. Castelo‘s book entitled ―História do Ensino no Ceará‖ (1970) figured as a turning-point for this study‘s initial chronology. The results here presented, which are consolidated by the core-curriculum of Fortaleza‘s Military School and by some students‘ statements, demonstrate that Middle Teaching offered by the School fulfilled the purposes to the National Military Institutions as it forms its students to serve the military career, as it made a register reservation for the Army and as it graduated most of this students for civil professional. The school was meant for military children, although the classes held in the period of 1962-1968 have had civilian students, in search of a civilian future, came from the high society of North and North-East Brazilian